2007
DOI: 10.1002/j.0022-0337.2007.71.9.tb04380.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between PBL Process Grades and Content Acquisition Performance in a PBL Dental Program

Abstract: In this study, we examined the relationship between students' problem-based learning (PBL) skills and their content acquisition as measured by traditional examinations. We conducted this investigation to evaluate the assumption that students' learning in the small group setting of PBL as evaluated by their faculty facilitators was an accurate indicator of students' learning as measured by problem analysis tests and traditional content acquisition tests. Parallel model reliability analyses were conducted to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 21 publications
0
22
0
8
Order By: Relevance
“…Brazilian medical students believe that subjectmatter experts perform better for guiding the learning process than their non-expert counterparts [9]. Other authors agree with this concept [5,28,29,35].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Brazilian medical students believe that subjectmatter experts perform better for guiding the learning process than their non-expert counterparts [9]. Other authors agree with this concept [5,28,29,35].…”
Section: Discussionmentioning
confidence: 96%
“…Correlations among methods of assessment in PBL are controversial. Von Bergmann et al [28] observed a significant relationship between facilitator's assessment of students based on their performance in tutorial groups and content acquisition examination. Yaqinuddin et al [5] also demonstrated strong association among PBL scores and written examinations, MCQ, short answer questions and OSCE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessment, monitoring, and programme evaluation all contribute to improving what and how students learn [ 7 ]. A number of publications have reported the effectiveness of the PBL process by measuring students’ satisfaction of the process from surveys [ 8 , 9 ], or the knowledge acquired by students as measured by examinations [ 10 – 12 ]. However, there is hardly any reported work that uses an independent PBL specialist to monitor performance of tutor and students during PBL tutorial sessions and how their performance affects the quantity and quality of hypotheses generated by the tutorial group.…”
Section: Introductionmentioning
confidence: 99%